Electromagnetic shielding properties of cementitious composites containing carbon nanofibers, zinc oxide, and activated carbon powder. (24th May 2021) - Wanasinghe, Dimuthu; Aslani, Farhad; Ma, Guowei
Highlights: Mechanical properties vary unpredictably with the addition of CNF, ZnO, and ACP. Mixes with ZnO shows best electrical conductivity compared to others. EMI SE increases in the order of ACP, ZnO, and CNF. EMI shielding is optimal when ACP combined with CF. SEM images how dense structure with random distribution of additives. Abstract: Exposure to electromagnetic radiation is known to cause many adverse effects such as malfunction of electronic devices and health problems in humans. Since currently used metallic shields suffer from various drawbacks, using construction materials that would provide the same amount of shielding has become a novel research area in the construction industry. Set of experiments were carried out to find the effect of carbon nanofibers, zinc oxide, and activated carbon powder on electromagnetic interference shielding in cementitious composites. Additionally, the impact of these additives on mechanical and electrical conductivity was measured. For these experiments, four different types of carbon nanofibers were used to establish the best type of carbon nanofibers. Different contents of each additive were mixed into the cementitious composite to find the optimal content of each additive. These three different types of additives were then combined with 12 mm unsized carbon fibre within the cementitious matrix. Effects of the hybrid composites were measured similar to previous tests to find out the best combination of additives that would provide the optimum amount of electromagnetic shielding. Electromagnetic shielding tests were carried out within the frequency range of 30 MHz to 1.5 GHz according to ASTM D4935 – 18 standard method. Results showed that the inclusion of individual additives did not have a significant impact on the electromagnetic shielding properties. The best shielding properties were obtained when 0.5% of activated carbon powder was combined with the carbon fibre, which was 42.5–60.0 dB.